An Empirical Investigation of EFL Teachers’ Digital Competences and Its Pedagogical Application - Salsabila, Fera; Mirizon, Soni; Vianty, Machdalena (Universitas Pendidikan Mandalika, 2025)
In an increasingly digital age, the integration of technology into education has become imperative, particularly in the domain of English language teaching. This study focuses on evaluating the digital competence of Junior high schools English teachers, with a primary emphasis on their proficiency and efficacy in utilizing digital tools within their teaching practices. Utilizing a qualitative research methodology, the study employed a combination of questionnaires and semi-structured interviews to assess teachers' digital skills. The study explored six core competence areas as delineated by the Digital Competence Framework for Educators (DigCompEdu), which include professional engagement, digital resources, teaching and learning, assessment, empowering learners, and facilitating learners' digital competence. The analysis revealed that English teachers demonstrate commendable digital competence, predominantly classified as